Optimized emitter contacting on multicrystalline silicon thin film solar cells. Issue 7 (18th June 2015) - Gawlik, A.; Höger, I.; Bergmann, J.; Plentz, J.; Schmidt, T.; Falk, F.; Andrä, G.
<x xml:space="preserve">Abstract</x> We present an optimized contacting scheme for multicrystalline silicon thin film solar cells on glass based on epitaxially crystallized emitters with a thin Al2O3 layer and a silver back reflector. In a first step a 6.5 µm thick amorphous silicon absorber layer is crystallized by a diode laser. In a second step a thin silicon emitter layer is epitaxially crystallized by an excimer laser. The emitter is covered by an Al2O3 layer with a thickness ranging from 1.0 nm to 2.5 nm, which passivates the surface and acts as a tunnel barrier. On top of the Al2O3 layer a 90–100 nm thick silver back reflector is deposited. The Al2O3 layer was found to have an optimal thickness of 1.5 nm resulting in solar cells with back reflector that achieve a maximum open‐circuit voltage of 567 mV, a short‐circuit current density of 27.9 mA/cm2, and an efficiency of 10.9%. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)